Cognitive and Neuronal Link With Inflammation: A Longitudinal Study in People With and Without HIV Infection. (15th December 2020) - Anderson, Albert M.; Jang, Jeong Hoon; Easley, Kirk A.; Fuchs, Dietmar; Gisslen, Magnus; Zetterberg, Henrik; Blennow, Kaj; Ellis, Ronald J.; Franklin, Donald; Heaton, Robert K.; Grant, Igor; Letendre, Scott L.
Abstract : Background: Across many settings, lack of virologic control remains common in people with HIV (PWH) because of late presentation and lack of retention in care. This contributes to neuronal damage and neurocognitive impairment, which remains prevalent. More evidence is needed to understand these outcomes in both PWH and people without HIV (PWOH). Methods: We recruited PWH initiating antiretroviral therapy and PWOH at 2 sites in the United States. One hundred eight adults were enrolled (56 PWOH and 52 PWH), most of whom had a second assessment at least 24 weeks later (193 total assessments). Tumor necrosis factor alpha, monocyte chemotactic protein-1 (MCP-1), neopterin, soluble CD14, and neurofilament light chain protein (NFL) were measured in plasma and cerebrospinal fluid (CSF). Using multivariate models including Bayesian model averaging, we analyzed factors associated with global neuropsychological performance (NPT-9) and CSF NFL at baseline and over time. Results: At baseline, higher CSF MCP-1 and plasma sCD14 were associated with worse NPT-9 in PWH, while CSF HIV RNA decrease was the only marker associated with improved NPT-9 over time. Among PWH, higher CSF neopterin was most closely associated with higher NFL. Among PWOH, higher CSF MCP-1 was most closely associated with higher NFL. After antiretroviral therapy initiation, decrease in CSF MCP-1 was most closely associated with NFL decrease. Conclusion: Monocyte-associated CSF biomarkers are highly associated with neuronal damage in both PWH and PWOH. More research is needed to evaluate whether therapies targeting monocyte-associated inflammation may ameliorate HIV-associated neurobehavioral diseases. Abstract : Supplemental Digital Content is Available in the Text.